Cherry tomato soilless cultivation method - WANG JIN; XU RU; LIN BIYING; ZHOU XIANGZHU; HUA WEIHUI; LIN YIZHANG; ZHENG TAO; LIU MINGYUE; ZHONG FENGLIN; JIA QI (2016)
The invention discloses a cherry tomato soilless cultivation method comprising the three aspects of soilless cultivation medium preparation, water-fertilizer integral application, and trimming and pruning. The soilless cultivation medium adopts a coconut coir composite medium. The trimming and pruning step comprises branch arrangement, trunk reservation, vine guiding, string hanging, flower and fruit management, and plant shape maintenance. According to the invention, the coconut coir composite medium is adopted, and irrigation water amount, fertilization amount, fertilization time and the like are controlled with the water-fertilizer integration technology, such that fertilizer-water management matches the trimming and pruning manner. With the method, tomato intrinsic growth and development characteristics can be developed; and the relationship between vegetative growth and reproductive growth is coordinated. The high-yield potential is explored while quality is improved. Also, facility and cultivation manag